ANALISIS IMPLIKASI PENGGUNAAN SMART BOARD TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMA - Husnul Khatimah; Farida Febriati (STKIP Subang, 2026)
he rapid development of information and communication technology (ICT) has significantly influenced classroom practices, including the teaching of mathematics at the senior high school level. One prominent form of ICT integration is the use of Smart Boards as interactive teaching media that combine the functions of a traditional whiteboard, projector, and computer in a single device. This study aims to analyse the implications of Smart Board use for improving senior high school students’ conceptual understanding of mathematics by examining cognitive, affective, and instructional process aspects. A library research design with qualitative content analysis was employed, drawing on empirical studies and conceptual papers on Smart Board and interactive whiteboard use in mathematics education at secondary and tertiary levels. Relevant journal articles, research reports, theses, and dissertations were systematically reviewed to identify patterns concerning the impact of Smart Boards on students’ conceptual understanding, motivation, engagement, and learning outcomes. The findings indicate that Smart Boards have positive implications for students’ conceptual understanding mainly through richer visual representation, the use of virtual manipulatives, clearer step-by-step demonstration of problem-solving processes, and enhanced teacher–student and student–student interaction in class. However, several studies also reveal that gains in test scores are not always statistically significant, suggesting that the effectiveness of Smart Board use strongly depends on pedagogical design, teachers’ technological and pedagogical competencies, and the meaningful integration of ICT into classroom activities. Overall, the study concludes that Smart Boards hold considerable potential to improve students’ conceptual understanding of mathematics at the senior high school level, provided that their use is systematically planned and supported by adequate infrastructure and sustained professional development for teachers.